THE ECONOMIC POWER OF VETO PLAYERS – THE CONNECTION BETWEEN FISCAL POLICIES, AND POLITICAL SYSTEMS - WASNIEWSK, Krzysztof (Theoretical and Practical Research in Economic Fields; Vol 7 No 2 (2016): TPREF, Volume VII, Issue 2(14), Winter 2016, 2016)
The present paper explores the correlation between political systems, and fiscal policies, focusing on those changes in fiscal policy that may be induced by modifications in the partisan structure of political systems, as compared to cross-sectional differences between constitutional systems. The government’s fiscal stance is studied chiefly as capital balances, rather than current flows. The theoretical model defines the possible appropriation of liquid assets in the public sector, starting from the basic fiscal equation. Empirical research consists of both a quantitative, econometric part, and qualitative case studies. Quantitative research allows concluding that political systems do differ as for the amount of liquid capital held by the public sector. Three broad clusters of countries are defined, regarding their political systems, and these clusters display a significant disparity as for their observable fiscal stance. Case studies sampled from those clusters lead to conclude that the amount of liquid assets held by the public sector changes in close correlation to political polarization. The main path open for future research is the question whether fiscal variables can indicate pre-emptively the emergence of political veto players, even before their official appearance in the partisan, or the constitutional structure.